The econocracy : the perils of leaving economics to the experts - Earle, Joe; Moran, Cahal; Ward-Perkins, Zach (Manchester capitalism., 2017)
A particular, narrow way of thinking about the economy is dominant in society today. This work explores how this came to be, why the system cannot continue and how to build a better future.